Analysis of community knowledge and understanding in terms of age level regarding the condition of the mangrove ecosystem in Tanjung Unggat Village, Tanjungpinang City - Nevrita Nevrita; Nurjanah Tri Wahyuni; Purba Erika; Ananda Erdi; Novianti Marsha; Afriana Dina (SHS Web of Conferences)
Mangrove ecosystems are an integral part of coastal ecosystems and have several ecological and economic benefits. However, the community's understanding of the mangrove ecosystem is still very shallow. This research aims to explore the Tanjung Unggat community's knowledge of the condition of the mangrove ecosystem. Data was collected through interviews and qualitative questionnaires. The method used is a simple qualitative method. The sampling technique is random sampling. Data collection using questionnaires and interviews. Research Results From the results of questionnaires that have been distributed to communities around the mangrove ecosystem, 33.33% of people aged 17-25 have knowledge of the mangrove ecosystem, while 23.67% of people aged 26-34 have knowledge, and 17 % aged 35-48 have the same knowledge about the mangrove ecosystem